„You go out and you hear it and this calls you, this is the mother tongue.“ Kotel Roma women‘s metadiscourses on language. - Salvatore, Camilla (Romano džaniben, 2025)
This article is based on a six-months ethnography at the “Center for work with street children” in Kotel - a small town in Bulgaria, presented by its municipality as an “example of understanding and integration of the Roma”. Sharing their daily tasks, I had the opportunity to observe how my Romani colleagues shift between using Bulgarian, the official language of the country, and Romani. When I asked them to explain how and why these shifts occurred, I discovered an “epilinguistic tension” (Canut, 1998) between adherence to the official norm and their desire to use their mother tongue. In this text, I describe how their meta-discourses about language refect the effects of linguistic policies and ideologies in past and present Bulgaria and two contrasting language ideologies related to notions of nationality, race/ethnicity, and citizenship. Adhering to the Center policy of using only Bulgarian but also expressing their desire to use their “mother tongue ” , my interlocutors are living an unresolved tension between assimilation and resistance, homogenization and emancipation.